Previous Employee Involvement in Pasuruan Bottled Drinking Water Supply Factory: Keterlibatan Karyawan Sebelumnya di Pabrik Pemasok Air Minum dalam Kemasan Pasuruan - Vania Rahma Nurhadiyanti; Rifdah Abadiyah (Universitas Muhammadiyah Sidoarjo, 2023)
This quantitative study explored the relationships between motivation, career development, job satisfaction, and employee engagement at PT. Erindo Mandiri (Aquase) Pasuruan. The research involved 134 randomly sampled employees who completed a Likert scale questionnaire. Using the SmartPLS program, structural equation modeling was employed to analyze the data. The results indicated significant effects of motivation and career development on job satisfaction and employee engagement. Furthermore, job satisfaction was found to mediate the influence of motivation and career development on employee engagement. These findings emphasize the importance of nurturing motivation, providing career development opportunities, and enhancing job satisfaction to foster higher levels of employee engagement. The implications suggest that organizations can utilize these insights to design targeted interventions and policies, creating a positive work environment that enhances employee well-being and contributes to improved organizational performance. Highlights: Motivation and Career Development: Key drivers of employee engagement. Job Satisfaction as a Mediator: Examining its role in linking motivation and career development to employee engagement. Implications for Organizational Performance: Utilizing findings to enhance employee engagement and promote positive work environments. Keywords: Motivation, Career Development, Job Satisfaction, Employee Engagement